The effects of fermented feed on broiler production and intestinal morphology - Naji, Saad A.; Al-Zamili, I. F. B.; Jawad, Hasan S. A.; Al-Gharawi, J. K. M. (Universiti Putra Malaysia Press, 2016)
The present experiment was conducted to evaluate the effects of wet feed and fermented feed on the intestinal morphology and histology of broiler chicks. A total of 360 one day old Ross 308 broiler chicks were randomly assigned (CRD) into six treatment groups. Chicks were fed: (T1) Control group of dry feed; (T2) Fed on wet feed (1:1, feed: water); (T3) 25% fermented feed + 75% dry feed; (T4) 50% fermented feed + 50% dry feed; (T5) 75% fermented feed + 25% dry feed and (T6) 100%, fermented feed throughout the experimental period. Each treatment group was replicated three times using 20 chicks per replicate. The chicks were raised at a temperature and in humidity controlled room with a 24-h. constant light and had ad. libitum access to water and feed throughout the experimental period which lasted for six weeks. The results showed that all diets containing fermented feed, especially 100%, had dependent effects on the evaluated production characteristics. The feeds had significantly (P < 0.05) increased the relative weight and length of the small intestine. Likewise, it raised the villi height, crypt depth and the percentage of the villi height to crypt depth in duodenum, jejunum and ileum increased. In conclusion, the results of the current experiment indicated that fermented feed with probiotic would be beneficial economically since the broiler feed conversion ratio had been improved (2.4% in T2; 4.1% in T3; 5.3% in T4; 5.3% in T5 and 7.7% in T6) as a consequence to enhance their intestinal morphology.